Risk of Material Misstatement in the Audit of Payments to Budget - Oleksandr Sherstiuk (Облік і фінанси)
Users of reporting, which is formed based on accounting data, can change the content and nature of their own decisions depending on the parameters of the information they receive. In other words, users' decisions depend on the values of specific indicators or their set. At the same time, such values are formed mainly based on the requirements imposed on reporting forms in regulatory and other documents that constitute the applied conceptual basis. During the audit, the auditor must remember that there is always a probability that the information disclosed in the reporting forms may contain material misstatements, which may lead to the auditor expressing an inadequate opinion on the quality of reporting. As a result, users of such reporting data may make ineffective decisions. The article aims to identify the risk of material misstatement of financial reporting information regarding the settlements of enterprises with the budget. The article presents a model of the risk of material misstatement of information regarding settlements within the budget. The model covers the localization of the risk, the causes of its occurrence, the substantive parameters of its elements, and possible consequences. The emphasis is on certain aspects of recognizing the risks of material misstatement, which are defined in the Handbook of International Quality Management, Auditing, Review, Other Assurance, and Related Services Pronouncements. The results of the study indicate that the statements of management personnel regarding data that can be used to identify the object of taxation, its measurement, the calculation of tax liabilities, as well as the state's debt and other settlements of the enterprise with the budget, characterize a wide range of signs of the existence of risks of material misstatement. The use of the proposed model will contribute to the optimization of the measures taken by the auditor to express a professional opinion on the reliability of the verified data. Thus, the results of this study are the basis for improving the methodical support of the audit as one of the mechanisms for increasing the level of public and state trust in the enterprise's reporting data.